Hidden in plain sight: A systematic review of coercion and Long-Acting Reversible Contraceptive methods (LARC). - Victoria Boydell; Robert Dean Smith; Global LARC Collaborative (GLC) (Public Library of Science (PLoS), 2023)
In recent years there has been extensive promotion of long-acting reversible contraceptives (LARC) globally to increase access to what is widely considered a highly effective contraceptive method. Yet, despite these efforts, evidence points towards the worrying propensity for LARCS to be associated with coercion. Hence, we undertook a meta-narrative review across nine databases to draw together the heterogeneous and complex evidence on the coercive practices associated with LARC programs. A total of 92 papers were grouped into three metanarratives: (1) law, (2) public health and medicine, and (3) the social sciences. Across disciplines, the evidence supports the conclusion that coercive practices surrounding LARC programs always target marginalized, disadvantaged and excluded population(s). Looking at coercion across disciplines reveals its many forms, and we present a continuum of coercive practices associated with LARC programming. We found that each discipline provides only a partial picture of coercion, and this fragmentation is a knowledge practice that prevents us from collecting accurate information on this subject and may contribute to the perpetuation of these suspect practices. We present this review to address longstanding silences around coercion and LARCs, and to encourage the development of clinical and programmatic guidance to actively safeguard against coercion and uphold reproductive rights and justice.